Protracted Conflicts, Crises, and Ethnicity:: The Arab-Israeli and India-Pakistan Conflicts, 1947-2005 - Ben-Yehuda, Hemda; Mishali-Ram, Meirav (Journal of Conflict Studies, 2006)
Abstract This study used international crisis as a tool to analyze Protracted Conflicts (PCs). Two core attributes, the compound nature and over all magnitude, were formulated and applied to the Arab-Israeli and India-Pakistan PCs in order to address three theoretical questions. First, how do we measure the compound nature of a PC and do PCs change over time? Second, how do we measure overall PC magnitude and does it change over time? Third, do the compound nature and magnitude of a PC correspond? We found that the concepts of compound nature and overall magnitude are useful and necessary tools for a systematic analysis of the two PCs in the Middle East and South Asia, over the years 1947- 2005. The two PCs are similar in some leading attributes (e.g. colonial tradition, religious and territorial stakes, nuclear complexity, outbreaks of violence and duration) but differ in others (salience of the ethnic and interstate dimensions, characteristics of ethnic actors, and overall magnitude). Regarding the correspondence between the compound nature and overall magnitude in PCs, we found some correspondence in both regional conflicts but not to the same degree. Given the importance of delineating PC dynamics, the study found that stability and order in the interstate domain cannot be detached from events that unfold in the ethnic-state domain. While outcomes of crises vary over time, compromise in ethnic-state confrontations was less evident than in interstate ones. The study concluded that a compound nature, or a primarily ethnic characterization of a conflict, not only prolongs the confrontation but also diminishes the prospects of conflict resolution. Notwithstanding the importance of territory, nuclear spread, and religion as core aspects in PCs, the study draws attention to ethnic actors and issues as salient aspects in international crises and conflicts, the heart and core of world politics.